MANAJEMEN PENANGGULANGAN KEMISKINAN: PENDEKATAN ELASTISITAS - LALU MUH. KABUL (Universitas Mahasaraswati Mataram, 2018)
The research stressed at poverty reduction management by using elasticity approach.The research method was mixing method: quantitative and qualitative. Data sources were primary and secondary data. For data collecting used interview and FGD. Growth elasticity of poverty, Pro-Poor Growth Index, Force Field Analysis were tools employed to analysis the data. The research results showed that themanagement strategy of poverty reduction is pro-poor. However, the stragey of poverty reduction in the future must be improved toward a growth oriented as well as environtmental friendly